(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The covid-19 pandemic came about a global health crisis, deeply impacting artistic and cultural activities worldwide, including Brazil. As a researcher, I felt the need to investigate the repercussions of this scenario on dance production. I conducted interviews with artists from the contemporary scene in São Paulo, including Mônica Augusto and Ivan Bernardelli, directors of Cia. Dual, to understand how they faced the challenges and redesigned their approaches in this unique reality. Their narratives unveil not only adaptation but also the resilience and reinvention required to survive and resist in this new context.